Numerical Simulation of Local Scouring on Pile Groups under Nonlinear Wave Action - ZHOU Xi; LI Xiaochao; GONG Mengmeng (Renmin Zhujiang)
Pile group foundations are widely used in coastal and marine engineering structures, and waves significantly affect the local scouring on pile group foundations. This article used the open-source computational fluid dynamics program REEF3D to establish a three-dimensional numerical wave tank. The inlet and outlet of the tank adopted the active absorption method and relaxation method separately to avoid the influence of reflected waves. Numerical simulations were conducted on the local scouring around a 2 × 4 pile group under nonlinear wave action, and the main water flow structures causing local scouring on the pile group, such as descending flow, horseshoe vortex, wake vortex, and gap flow, were calculated and simulated. The calculation results indicate that changes in the vertical velocity of water quality points in waves can cause variations in the descending flow and horseshoe vortex intensity. Within the KC number range (14.28–63.96) studied in this article, both the descending flow and the horseshoe vortex are weak and not the dominant factors of scouring. When the KC is small, the scouring is mainly controlled by the gap flow, and the maximum scouring depth occurs in the area between the left and right sides of the first row of piles in the upstream area. As the KC number increases, the wake gradually becomes the dominant driving factor for scouring, and the location of the maximum scouring depth gradually shifts to both sides of the first row of piles. The variation law of the maximum dimensionless scouring depth with KC number when reaching equilibrium is similar to that of a single pile. The variation law of the maximum scouring depth around each row of piles in a pile group is related to the nonlinearity of the waves. When the nonlinearity is weak, the scouring on the two rows of piles in the upstream and downstream areas is stronger than that of the piles in the middle. When the nonlinearity is strong, the dominant effect of forward water flow in one cycle is enhanced. Due to the shielding effect of the front piles, the scouring depth of the rear piles decreases.